Animal diversity of nauradehi wild life sanctuary Sagar (M.P.) - K. Napit, M. (Scientific Journal of Zoology, 2013)
Wild life conservation includes all human efforts to preserve wildanimals from extinction. It involves the protection and wise management of wildspecies and their environment. Some species have become extinct due to naturalcauses but the greatest danger to wild life result from human activities. Thuswe ourselves have created this need for wild life conservation. The progress ofman throughout has been beneficial for the human race but it is the wild thathas suffered through the years. Invention of sophisticated weapons,industrialization, urbanization, ever increasing human population have beensome of the major causes for the dwindle of our once rich wild life resource.Hunting, clearing of forests, draining of swamps and damming of rivers forirrigation and industry, this is what we apprise of man’s progress. Theseactivities have vastly reduced the natural habitats of our wild life and manyspecies are endangered or nearly extinct.